Light‐responsive microRNA miR‐211 targets Ezrin to modulate lysosomal biogenesis and retinal cell clearance. (10th March 2020) - Naso, Federica; Intartaglia, Daniela; Falanga, Danila; Soldati, Chiara; Polishchuk, Elena; Giamundo, Giuliana; Tiberi, Paola; Marrocco, Elena; Scudieri, Paolo; Di Malta, Chiara; Trapani, Ivana; Nusco, Edoardo; et al.
Abstract: Vertebrate vision relies on the daily phagocytosis and lysosomal degradation of photoreceptor outer segments (POS) within the retinal pigment epithelium (RPE). However, how these events are controlled by light is largely unknown. Here, we show that the light‐responsive miR‐211 controls lysosomal biogenesis at the beginning of light–dark transitions in the RPE by targeting Ezrin, a cytoskeleton‐associated protein essential for the regulation of calcium homeostasis. miR‐211‐mediated down‐regulation of Ezrin leads to Ca 2+ influx resulting in the activation of calcineurin, which in turn activates TFEB, the master regulator of lysosomal biogenesis. Light‐mediated induction of lysosomal biogenesis and function is impaired in the RPE from miR‐211 −/− mice that show severely compromised vision. Pharmacological restoration of lysosomal biogenesis through Ezrin inhibition rescued the miR‐211 −/− phenotype, pointing to a new therapeutic target to counteract retinal degeneration associated with lysosomal dysfunction. Synopsis: MicroRNA‐204/211 (miR‐211) are expressed in murine retinal pigment epithelium (RPE) and regulate eye differentiation and function. Light‐activated miR‐211 targets the membrane/cytoskeleton‐crosslinking protein Ezrin to activate the calcineurin/TFEB pathway in the RPE, thereby inducing lysosomal biogenesis and the degradation of photoreceptor outer segments (POS). Light‐responsive miR‐211 is required for daily lysosomal biogenesis and function in the RPE by targeting Ezrin. miR‐211‐induced downregulation of Ezrin promotes the release of lysosomal Ca 2+ through TRPML1, which triggers TFEB nuclear translocation and Calcineurin‐mediated activation of CLEAR network. miR‐211 −/− mice show impaired lysosomal degradation of POS and a progressive accumulation of lipofuscin in the RPE that resembles human age‐related macular degeneration (AMD) disease. Pharmacological inhibition of Ezrin in miR‐211 −/− mice rescues these defects, pointing to a new therapeutic target to counteract AMD onset and progression. Abstract : Downregulation of the membrane/cytoskeleton‐crosslinking protein Ezrin activates the calcineurin/TFEB pathway to promote lysosomal degradation of photoreceptor outer segments in murine retinal pigment epithelium cells.